INFLUENCE OF STRATEGIC LEADERSHIP ON STRATEGY IMPLEMENTATION IN THE KENYAN MOTOR VEHICLE INDUSTRY - Njeri, Benjamin N (European Journal of Business and Strategic Management, 2017)
Purpose: The main purpose of this study was to establish the influence of strategic leadership on strategy implementation in the Kenyan motor vehicle industry. Methodology: The study was carried out using descriptive research design. The target population for this study was 13 major motor vehicles retailers in Kenya as listed in the KMI website. . The sampling frame of this study was the various management levels of the 13 major motor vehicles retailers in Kenya as listed on the KMI association website. Stratified random sampling was used. . The study used questionnaires to collect the required data. Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Regression and Correlation analysis was used to establish the relationship between the independent and dependent variables. Results: The study findings revealed that a positive and significant relationship between strategic leadership as represented by leadership competence, leadership communication, personnel involvement, as wells monitoring and evaluation and strategy implementation has been established. Policy recommendation: The study recommended that firms prioritize on the enhancement leadership capacities in terms of the formulation and implementation of strategies. Moreover, organizations can invest in measures aimed at improving the existing working relationship of leaders with their juniors and superiors. The study also recommends that Organizations emphasize on effective communication to get the right message across to the right people through the right channels. Furthermore, Leaders should foster a culture of inclusivity in their decision-making as this makes it easier to implement those decisions. Organizations will succeed more where they treat employees as major stakeholders in the business and take concrete steps to motivate them as well as listen to their views on a given strategy